Soil and leaf phosphorus thresholds for modern potato production systems in tropical Oxisols - Soratto, Rogério P. [UNESP]; Sandaña, Patricio; Fernandes, Adalton M. [UNESP]; Calles, Tassiane S. [UNESP]; Yagi, Renato; Souza, Emerson F.C.; Job, André L.G.; Martins, Jéssyca D.L. [UNESP] (Elsevier, 2023)
Precise diagnosis and prognosis of phosphorus (P) nutrition are essentials to improve P use efficiency and sustainability in potato cropping systems. Here, variable potato crop responses of 13 field experiments (2011–2022) were assessed to determine critical soil P-resin (SPresin) and potato leaf P (LP) concentrations to achieve maximum tuber yield in tropical Oxisols. The study comprised four experiments with the factorial design of potato cultivars in response to P fertilization rates and nine experiments with P fertilization rates as fixed effects. Relationships between initial SPresin test, LP measured at the third or fourth expanded leaf stage (i.e., 29–37 days after emergence, DAE), and relative total fresh tuber yield (RY) (yield of control/yield at highest P rate) were analyzed using linear-plateau, Mitscherlich, and quadratic-plateau regression models. A wide range of total fresh tuber yield (3.2–59 Mg ha-1) and LP (1.3–5.7 g P kg-1) were observed across experiments. The LP values in control plots was positively related with initial SPresin, reaching a maximum LP of 3.8 g P kg-1 at an initial SPresin of 80 mg P dm-3 (averaged across models). The relationship between RY and initial SPresin was significant in the three regression models (p < 0.05; R2 = 0.71–0.74). Maximum tuber yield was reached with the SPresin value of 93 mg P dm-3 (averaged across models). Across experiments and P fertilization rates, relationships between RY and LP were significantly described in the three regression models (p < 0.05; R2 = 0.55–0.67). The critical LP of 4.5 g P kg-1, obtained from the average across models, is proposed as the optimum indicator of potato P nutritional status to achieve maximum tuber yields in tropical Oxisols. These are the first critical P thresholds on a soil and environmental-specific conditions base available for tropical conditions in Brazil, timely informative in terms of optimization of P management to maximize tuber yield and P use efficiency, and minimize the risk of environmental P contamination.
Keywords: Critical threshold; Fertilization efficiency; Phosphorus nutrition; Solanum tuberosum